Comparing TensorFlow and PyTorch for Image Recognition in NAO Robot Soccer - Souza, Vitor Amadeu; Sá, Hebert Azevedo (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2025: Anais do LII Seminário Integrado de Software e HardwareDO - 10.5753/semish.2025.7943, 2025)
The study compares TensorFlow and PyTorch in image recognition tasks within NAO robot soccer. Image classes were created and trained using data augmentation to enhance robustness and generalization. The analysis considered training time, classification accuracy, and adaptability to different lighting conditions and angles. The results showed that TensorFlow outperformed PyTorch, achieving higher accuracy and better adaptation to challenging scenarios, making it more suitable for computer vision in dynamic environments. The novelty of this study lies in evaluating these frameworks on the NAO robot’s specific hardware, under realistic robotic conditions.